2022
DOI: 10.3390/ijerph19063514
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence, Psychological Well-Being and Burnout of Active and In-Training Teachers

Abstract: The main activating variables of psychological well-being and Emotional Intelligence that influence teachers include the process of evaluating well-being, their motivation, and their ability to perceive and regulate sources of stress and burnout. The relationship and influence of psychological well-being and emotional intelligence was analyzed with the adequate regulation of burnout. Those who participated included 386 active teachers (55%), and teachers in training (45%), studying for degrees in Pre-School an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
19
0
4
Order By: Relevance
“…Very dissimilar results were found by Martínez-Rubio et al [ 49 ], who stated that the practice of physical exercise can reduce stress levels and, therefore, channel burnout syndrome. Physical exercise brings numerous benefits to emotional development, helping to improve mood and attitude when facing tasks [ 6 , 50 ]. In addition, it was observed that a longer time spent preparing for a task leads to higher levels of burnout [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very dissimilar results were found by Martínez-Rubio et al [ 49 ], who stated that the practice of physical exercise can reduce stress levels and, therefore, channel burnout syndrome. Physical exercise brings numerous benefits to emotional development, helping to improve mood and attitude when facing tasks [ 6 , 50 ]. In addition, it was observed that a longer time spent preparing for a task leads to higher levels of burnout [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salas-Vallina et al suggested that the absence of EE is a dimension of employee WB [ 69 ]. Lucas-Mangas et al argued that EE is significantly negatively correlated with WB and factors related to WB [ 103 ]. If the work environment can reduce employees’ EE, it can increase their WB and job satisfaction [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, la práctica de actividad física y su asociación con el síndrome de Burnout y la Inteligencia Emocional en docentes (tablas 5 y 6) es un ámbito poco estudiado. Tabla 5 Evolución de la producción científica del Síndrome de Burnout y actividad física en el ámbito docente Tabla 6 Evolución de la producción científica de la Inteligencia emocional y actividad física en el ámbito docente De los resultados extraídos y de las evidencias científicas encontradas, son diversos los estudios que manifiestan que la inteligencia emocional ejerce como factor de protección ante la aparición de síntomas de Síndrome de Burnout (Lucas-Mangas et al, 2022;Puertas-Molero et al, 2019;Schoeps et al, 2021). Es por ello, que autores como Martínez-Monteagudo et al (2019) o Suárez-Martel y Martín-Santana (2019), manifiestan que los docentes con una baja inteligencia emocional general se asocian con el agotamiento emocional, despersonalización, estrés, ansiedad, depresión y escasa realización personal.…”
Section: Tabla 3 Evolución De La Producción Científica De La Intelige...unclassified
“…Llegados a este punto, entra en juego un aspecto esencial como son las emociones, concretamente la inteligencia emocional, entendida esta como la habilidad de percibir, valorar y expresar las emociones con eficacia (Meléndez et al, 2019;Salovey y Mayer (1990). De hecho, dentro del contexto educativo la Inteligencia Emocional lleva unos años adquiriendo una especial relevancia, ya que se asocia con grandes beneficios en lo que, a capacidad de resiliencia, toma de decisiones bajo situaciones estresantes, bienestar mental y regulación de sentimientos se refiere (Kamboj y Garg, 2021;Lucas-Mangas et al, 2022).…”
Section: Introductionunclassified